Sustainability as a multi-criteria concept: new developments and applications - Luis Díaz Balteiro; Jacinto González-Pachón; Carlos Romero (MDPI, 2020)
Sustainability is a fairly old concept, born in the 18th century in the field of forestry, within a mono-functionality perspective. The concept has considerably evolved in the last few years towards a multi-functionality context, with applications reported in practically all areas of economic interest. On the other hand, modern sustainability is a complex problem, for two reasons: a) The multiplicity of functions of a very different nature involved in the process and b) The manner in which different segments of the society or stakeholders perceive the relative importance of these functions. For the above reasons, a realistic approach for dealing with the sustainability issue requires taking into consideration multiple criteria of different nature (economic, environmental and social), and in many cases within a participatory decision making framework. This book presents a collection of papers, dealing with different theoretical and applied issues of sustainability, with the help of a modern multi-criteria decision-making theory, with a single as well as several stakeholders involved in the decision-making process. Hopefully, this material will encourage academics and practitioners to alter their research in this hot and vital topic. A􀀿er all, the sustainable management of the environment and its embedded resources is one of the most important, if not the major challenge of the 21st century.
Keywords: 330; Multiple Criteria Decision Making; Indicators and Synthetic Indices; Sustainability Measurement; Rankings in terms of Sustainability; Environmental and Natural Resources Economics; Collective Decision Making